A review of the principle of good faith in English Contract Law / Bryan Ching-Wing Lo - Lo, Bryan Ching-Wing (Universiti Teknologi MARA, Perlis, 2011)
Today, the question of "Is there a duty to negotiate in good faith?" still arises in most of the jurisdictions that practice English Law. This paper reviews the principle of good faith in English contract law to provide an insight of how the UK courts make judgment decisions. The main reference case to support this research paper is Walford v Miles which had been cited by many jurisdictions for their previous court decisions. Other sources of references were derived from legal journal articles and books. In the discussion, there were findings both supporting and rejecting the "agreement to agree". However, the final outcome of the analysis revealed that a more explicit definition by the UK law is required to end the debate on the principle vagueness.